2020
DOI: 10.1093/pcp/pcaa103
|View full text |Cite
|
Sign up to set email alerts
|

The VvSUPERMAN-like Gene Is Differentially Expressed between Bicarpellate and Tricarpellate Florets of Vitis vinifera L. Cv. ‘Xiangfei’ and Its Heterologous Expression Reduces Carpel Number in Tomato

Abstract: Multicarpellate fruits are larger and produce more seeds than mono- or bicarpellate fruits, enhancing the reproductive capacity of the plant. To identify the phenotypic and molecular differences among florets of different carpel types, we studied carpel formation and fusion in the grapevine (Vitis vinifera) cultivar ‘Xiangfei’, which produces a high proportion of multicarpellate fruit. We also determined the function of VvSUPERMAN-like (VvSUP-like) and explored its relationship with VvWUS (VvWUSCHEL) and VvAG1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The prepared paraffin sections were observed and photographed using an Olympus CX31 microscope (Olympus Corporation, Tokyo, Japan). The processes of dehydration and transparency were carried out according to the method described by Liang et al [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prepared paraffin sections were observed and photographed using an Olympus CX31 microscope (Olympus Corporation, Tokyo, Japan). The processes of dehydration and transparency were carried out according to the method described by Liang et al [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The transgenic plants were cultured in an artificial climate incubator HPG-280 HX (HDL, Changzhou City, China) with the 16 h light/8 h dark photoperiod. The transgenic methods were described as Liang et al [ 18 ]. The wild-type Micro-Tom tomato was used as the negative control for the tomato transformation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene SUPERMAN ( SUP ) is a negative repressor of WUS . In grapes ( Vitis vinifera , Vitaceae), multicarpellate berries develop in plants with reduced expression of VvSUP-like [ 55 ]. It was confirmed that VvSUP-like prevents the expression of grape orthologues of SUP targets VvAG1 and VvWUS [ 55 ].…”
Section: Fm Should Not Proliferate For Too Long: Ag/wus ...mentioning
confidence: 99%
“…In grapes ( Vitis vinifera , Vitaceae), multicarpellate berries develop in plants with reduced expression of VvSUP-like [ 55 ]. It was confirmed that VvSUP-like prevents the expression of grape orthologues of SUP targets VvAG1 and VvWUS [ 55 ]. As tri- and tetracarpellate berries are larger, this feature is of agricultural value.…”
Section: Fm Should Not Proliferate For Too Long: Ag/wus ...mentioning
confidence: 99%